The Role Of Al-Hidaya By Burhanuddin Al-Marghinani In The Science Of Hilyaf - Gadzhiev Mavlidin Gadzhievich (Indonesian Culture and Religion Issues, 2025)
The article describes “Al-Hidaya” (The Guidance), authored by Burhanuddin al-Marghinani in the 12th century, which is a seminal work in Islamic jurisprudence, particularly within the Hanafi school of thought. This comprehensive legal text has significantly influenced the science of hilyaf, which studies legal disagreements among various Islamic scholars and schools of thought (mazhabs). This article explores the impact of "Al-Hidaya" on the science of hilyaf, highlighting its contributions to legal interpretation, conflict resolution, and the development of Islamic jurisprudence. Employing qualitative, historical, and comparative methodologies, the study reveals that "Al-Hidaya" systematically presents legal opinions, aids in resolving legal disputes, and has influenced later works. Its methodological contributions, including the use of qiyas (analogy), istihsan (preference), and ijma (consensus), promote flexibility and inclusivity in legal interpretation. "Al-Hidaya" remains a vital resource for scholars, offering a comprehensive framework for understanding and navigating legal differences, thereby contributing to a more cohesive and harmonious Islamic legal tradition.